A preparation method for constructing strong magnetocrystalline coupling alloy

By replacing Ge with Co element in Tb5Si2Ge2 alloy, Tb5Si2Ge(2-x)Cox alloy was prepared, and the problems of material brittleness and strong magnetic crystal coupling were solved, and the magnetic entropy change and temperature average entropy change were improved significantly. Magnetic refrigeration performance and material stability.

CN116287922BActive Publication Date: 2024-12-27HANGZHOU DIANZI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310297967.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-24
Publication Date
2024-12-27
Estimated Expiration
2043-03-24

AI Technical Summary

Technical Problem

When constructing strong magnetic crystal coupling, existing magnetic refrigeration materials have problems such as material brittleness leading to cracking of the refrigeration work fluid, and when the pressure is removed after hydrostatic pressure is applied, the strong magnetic crystal coupling cannot be permanently maintained, which affects practical application.

Method used

By replacing Ge elements with Co elements in Tb5Si2Ge2 alloy, Tb5Si2Ge(2-x)Cox alloy is prepared by using the precise ratio of high-purity Tb, Si, Ge and Co elements and the cold crucible suspension smelting method to achieve magnetic order phase change and The synchronous structure phase change occurs, and the magnetic performance is measured using a superconducting quantum interferometer and the magnetic entropy change is calculated to improve the refrigeration capacity.

Benefits of technology

A significant increase in magnetic entropy change in the magnetic field range of 0 to 5T was achieved, and the average temperature entropy change value was increased, and a stable strong magnetic crystal coupling material was obtained, which enhanced the magnetic refrigeration performance of the material and avoided the risk of cracking of the refrigeration work fluid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116287922B_ABST
    Figure CN116287922B_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation method for constructing a strong magnetocrystalline coupling alloy, comprising the following steps: step 1, according to Tb5Si2Ge (2‑x) Co x The alloy molecular formula uses high-purity Tb, Si, Ge and Co elements for precise proportioning. According to the required sample weight requirements, each raw material is weighed, mixed evenly and placed in a crucible of a smelting furnace. The furnace chamber is then sealed, an inert gas is introduced, the temperature is raised for smelting, and the alloy is cooled to room temperature in an inert gas environment. According to the above steps, the sample orientation is adjusted, and the smelting is repeated 4-5 times to obtain an alloy ingot; step 2, using a superconducting quantum interference device to measure the magnetic properties of the alloy; step 3, using Maxwell's relationship, numerical integration is performed to obtain the magnetic entropy change ΔSM of the alloy, and then the temperature average entropy change is used to determine the refrigeration capacity of the alloy. The preparation method of the present invention is simple, and has significant advantages in energy saving, safety, greenness and environmental protection in the field of magnetic refrigeration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of magnetic refrigeration materials, in particular to a preparation method for constructing a strong magneto-crystalline coupling alloy. Background Art

[0002] Magnetic refrigeration is a green solid-state refrigeration technology that is very promising to replace traditional gas refrigeration. Therefore, it has attracted widespread attention from countries around the world in basic scientific research, technology development and commercial promotion. Magnetic refrigeration technology usually uses a magnetic field to drive the phase change of magnetic materials, and uses the materials to release and absorb the latent heat of phase change during the magnetization and demagnetization stages to ultimately achieve the purpose of refrigeration. Magnetocrystalline coupling materials in which magnetic ordered phase change and structural phase change occur simultaneously are widely used in this technology. By constructing strong magnetocrystalline coupling, when the material undergoes a magnetic phase change, a large change in magnetization intensity (ΔM) and a strong magnetocaloric effect can be obtained. At the same time, the crystal structure phase change can also be accompanied by more phase change latent heat, thereby improving the overall thermal effect. In addition, a large ΔM can also enhance the ability of the magnetic field to drive the phase change, so constructing a strong magnetocrystalline coupling is an effective way to achieve excellent low-field magnetic refrigeration performance.

[0003] Tb5Si2Ge2 is a type of rare earth alloy with rich magnetic phase transitions and large magnetization intensity. It has a low-temperature orthorhombic structure (O(I), Pnma) and a high-temperature monoclinic structure (M, P1121 / a). During the heating process, the alloy successively undergoes a phase transition process from O(I) ferromagnetism → M ferromagnetism → M paramagnetism. Specifically, Tb5Si2Ge2 undergoes a first-order phase transition from a low-temperature ferromagnetic orthorhombic O(I) phase to a high-temperature ferromagnetic monoclinic M phase at around 92K, accompanied by a smaller ΔM, which manifests as magnetocrystalline decoupling. Although the magnetic entropy change and lattice entropy change of the alloy have the same sign, it does not mean that this structural phase transition can bring about a large low-field total entropy change. If we use appropriate methods to adjust the structural phase transition in the low-temperature zone to between the O(I) phase ferromagnetism and the M phase paramagnetism, then we can not only retain the larger lattice entropy change ΔS L , and can also bring about large ΔM and large magnetic entropy change ΔS Mand a small driving field. In 2004, "Pressure enhancement of the giant magnetocaloric effect in Tb5Si2Ge2[J], L.Morellon et al., Physical Review Letters, 2004, 93:137201" researchers proposed to construct strong magnetocrystalline coupling in Tb5Si2Ge2 by applying hydrostatic pressure, and effectively improved the total entropy change. However, this method requires continuous pressure loading during operation, and because the material has a certain brittleness, it is easy to cause cracking of the refrigerant. In addition, when the pressure is removed, the constructed strong magnetocrystalline coupling immediately returns to decoupling and cannot permanently maintain a stable strong coupling state. The above factors have brought difficulties to the practical application of constructing strong magnetocrystalline coupling. Therefore, it is necessary to explore new ways to construct strong magnetocrystalline coupling.

[0004] We know that if other elements are used to replace Si or Ge in the alloy, chemical pressure can be continuously provided in the alloy, and it is expected that the structural phase transition temperature will fall between O(I) ferromagnetism and M paramagnetism, thereby obtaining a stable coupling of magnetic phase transition and structural phase transition. The present invention uses a small amount of magnetic Co element to replace the Ge element in the Tb5Si2Ge2 alloy material, thereby obtaining a stable strong magnetocrystalline coupling material. At the same time, so far, in Tb5Si2Ge2 alloy, there has been no report on the use of the method of doping Co element to construct magnetic structural coupling phase transition and enhance magnetocaloric effect. Summary of the invention

[0005] The purpose of the present invention is to provide a preparation method for constructing a strong magnetocrystalline coupling alloy, by which the magnetic ordering phase transition and structural phase transition of the Tb5Si2Ge2 alloy material can occur synchronously, and the magnetic entropy change ΔS of the Tb5Si2Ge2 alloy can be reduced. M A greater improvement is obtained, thereby improving the refrigeration capacity of the material.

[0006] The technical solution of the present invention is a preparation method for constructing a strong magnetocrystalline coupling alloy, comprising the following specific steps:

[0007] Step 1, based on Tb5Si2Ge (2-x) Co x The alloy molecular formula uses high-purity Tb, Si, Ge and Co elements for precise proportioning. According to the required sample weight requirements, weigh each raw material, mix them evenly and place them in the crucible of the smelting furnace. Then seal the furnace chamber, introduce inert gas, heat and melt, and cool to room temperature in an inert gas environment. According to the above steps, adjust the sample direction, and repeat the smelting 4-5 times to obtain an alloy ingot;

[0008] Step 2, using a superconducting quantum interference device (SQUID) to measure the magnetic properties of the alloy;

[0009] Step 3: Using Maxwell's relation, numerical integration is performed to obtain the magnetic entropy change ΔS of the alloy. M , and then use the temperature averaged entropy change (TEC) to determine the refrigeration capacity of the alloy.

[0010] The present invention further comprises that in step 1, the smelting method is cold crucible suspension smelting, and the inert gas is high-purity argon.

[0011] The present invention further comprises that in step 2, a superconducting quantum interference device (SQUID) is used to measure the thermomagnetic magnetization (MH) curve of the sample.

[0012] The present invention further comprises that in step 3, the magnetization (MH) curve is obtained by using step 2, and then according to the Maxwell relation Calculate the magnetic entropy change ΔS of the alloy M , where T is the test temperature, H is the magnitude of the external magnetic field, and μ0 is the vacuum permeability. In order to evaluate the refrigeration capacity, the temperature average entropy change (TEC) is introduced and written as Here ΔT lift and T mid Respectively represent the temperature range and center temperature, ΔS(T) ΔH It represents the entropy change value of the variable magnetic field at a specific temperature.

[0013] Beneficial effects of the present invention:

[0014] (1) The preparation method of the present invention can transform the Tb5Si2Ge2 decoupled alloy into a strong magnetocrystalline coupled alloy. In the magnetic field range of 0 to 5 T, the maximum value of the isothermal magnetic entropy change is -18.30 Jkg -1 K -1 Increased to -31.34Jkg -1 K -1 The average entropy change value TEC(3) of temperature has a certain increase under different magnetic field changes, and the maximum value is 17.69 Jkg -1 K -1 Increased to 30.19 Jkg -1 K -1 This shows that the introduction of a small amount of Co element can greatly improve the magnetic refrigeration capacity of the material.

[0015] (2) The traditional method is to construct strong magnetocrystalline coupling by applying hydrostatic pressure, and the total entropy is significantly improved. However, this method has obvious defects. In addition to the need to continuously apply pressure, the pressure can easily cause the refrigerant to crack. The preparation method of the present invention can obtain stable strong magnetocrystalline coupling materials. This method can further explore the magnetocaloric properties of more materials, thereby accelerating the rapid development of magnetic refrigeration technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 MT curves and (dM / dT)-T curves of comparative examples and example alloys of the present invention at different temperatures.

[0017] Figure 2 It is a schematic diagram of the magnetic phase transition and structural phase transition from decoupling to strong coupling in the present invention.

[0018] Figure 3 It is a curve diagram of the magnetic entropy change of the comparative alloy of the present invention under different magnetic field changes as a function of temperature.

[0019] Figure 4 It is a curve diagram of the magnetic entropy change of the alloy of the embodiment of the present invention under different magnetic field changes as a function of temperature.

[0020] Figure 5 It is a comparison diagram of the average entropy change of temperature of the comparative example and example alloys of the present invention under different magnetic field changes. DETAILED DESCRIPTION

[0021] The present invention will be further described below in conjunction with the accompanying drawings and specific implementation methods.

[0022] Comparative Example

[0023] In this comparative example, the preparation method and performance characterization of the Tb5Si2Ge2 alloy material include the following steps in sequence:

[0024] Step 1: According to the alloy molecular formula, use high-purity Tb, Si, and Ge elements for precise proportioning. According to the required sample weight requirements, weigh each raw material, mix them evenly and place them in the crucible of the smelting furnace. Then seal the furnace chamber, pass high-purity argon gas, heat and melt, and cool to room temperature in a high-purity argon environment. According to the above steps, adjust the sample direction, and repeat the smelting 4-5 times to obtain an alloy ingot;

[0025] Step 2, using a superconducting quantum interference device (SQUID) to measure the magnetic properties of alloys with different compositions and obtain magnetization (MH) curves at different temperatures;

[0026] Step 3, using the magnetization (MH) curve from step 2, and then according to Maxwell's relationship Calculate the magnetic entropy change ΔS of the alloyM , where T is the test temperature, H is the magnitude of the external magnetic field, and μ0 is the vacuum permeability. In order to evaluate the refrigeration capacity, the temperature average entropy change (TEC) is introduced and written as Here ΔT lift and T mid Respectively represent the temperature range and center temperature, ΔS(T) ΔH It represents the entropy change value of the variable magnetic field at a specific temperature.

[0027] Example

[0028] Tb5Si2Ge (2-x) Co x (x=0.1-0.2) Preparation method and performance characterization of alloy material. The preparation method of this embodiment is different from that of the comparative example only in that a small amount of Ge element in step 1 is replaced by a small amount of Co element.

[0029] Figure 1 It is the MT curve and (dM / dT)-T curve diagram of the comparative examples and embodiments of the present invention at different temperatures. According to the first-order derivative dM / dT of the change of magnetization intensity with temperature, it can be seen that when the temperature reaches 92K, the dM / dT value of the comparative sample begins to decrease, indicating that the magnetization intensity of the sample begins to decrease at this time. Further increasing the temperature, the magnetic moment of the comparative sample drops significantly, and dM / dT shows a peak at 110K. The comparative alloy usually undergoes a primary phase transition from O(I) ferromagnetic phase to M ferromagnetic phase near 92K. This structural phase transition and magnetic phase transition show decoupling characteristics, so the magnetic moment near 92K does not drop significantly. However, as the temperature increases, during the structural phase transition, after entering the M phase, the sample immediately undergoes a secondary phase transition from ferromagnetic to paramagnetic, and its Curie temperature About 110K. Figure 2 The schematic diagram shows the phase transition process of Tb5Si2Ge2 alloy from O(I) ferromagnetism to M ferromagnetism to M paramagnetism after heating from low temperature. It can be seen that Tb5Si2Ge2 undergoes a first-order phase transition from low-temperature ferromagnetic orthorhombic O(I) phase to high-temperature ferromagnetic monoclinic M phase at around 92K ( Figure 2 ①), accompanied by a smaller ΔM, showing magnetocrystalline decoupling behavior.

[0030] For the example sample, we found that the dM / dT value did not decrease at 92K, and the magnetization intensity of the sample began to gradually decrease until the temperature reached 107K. When the temperature was further increased, the magnetization intensity showed a steep drop phenomenon, and dM / dT reached a peak at 116K. Obviously, the MT curve of the example sample is significantly different from that of the comparative example sample. The phase transition temperature of the example sample is increased and the phase transition temperature range is narrowed. Figure 2As shown in the figure, the Co-doping method actually adjusts the structural phase transition from ① to ②, that is, directly transforms from the ferromagnetic state of the O(I) phase to the paramagnetic state of the M phase, and a magnetic structural coupling phase transition of O(I) ferromagnetic → M paramagnetic occurs at 116K.

[0031] In order to verify the intensity of the magnetocaloric effect of the comparative example and the embodiment, we used the Maxwell relationship to calculate the entropy change data of the comparative example and the embodiment under different magnetic field changes, such as Figure 3 and 4 As shown. It can be clearly seen that within a certain temperature range, both the comparative example and the embodiment have obvious magnetocaloric effect. And as the variable magnetic field gradually increases, the peak value of the magnetic entropy change of the comparative example and the embodiment also gradually increases. For the comparative example samples, the peak value of the magnetic entropy change with a higher ΔH does not fall within the Curie temperature of the M phase of the secondary phase transition. Nearby, but falls at the structural phase transition temperature T s and 100K between. This phenomenon may come from the fact that the structural phase transition and the pure magnetic phase transition occur in series, that is, during the process of the first-order phase transition of O(I) ferromagnetism → M ferromagnetism (still in the coexistence zone of M and O(I) phases), the second-order phase transition of M ferromagnetism → M paramagnetism began to occur, and finally the magnetization intensity showed the largest decrease amplitude near 100K as the temperature increased, so the peak value of magnetic entropy change fell near 100K. For the example sample, its magnetic entropy change peak only falls on its structural phase transition temperature of 116K, which also shows that the sample no longer has the characteristic of two phase transitions occurring in series, and basically only a pure magnetic structural coupling phase transition occurs. As can be seen from the figure, when the external magnetic field is 5T, the maximum value of the magnetic entropy change of the comparative example and the example reaches -18.30Jkg respectively. -1 K -1 and -31.34Jkg -1 K -1 Compared with the comparative example, the magnetic entropy change of the embodiment is increased by 71.26%, which further illustrates that the Co-doping method can enhance the magnetocaloric effect of the Tb5Si2Ge2 alloy system.

[0032] Figure 5 The data of TEC (3) of the comparative example and the embodiment are shown. It can be clearly seen that compared with the comparative example, the embodiment has a larger TEC value under each magnetic field. For example, under a 5T variable magnetic field, the TEC (3) of the embodiment is 30.19 Jkg -1 K -1 , compared with the comparative example (19.69 Jkg -1 K -1) is nearly 70.7%. In addition, the slope of the TEC of the embodiment with the change of magnetic field is also larger than that of the comparative example, which may be due to the fact that the magnetic field drives the structural phase change synchronously to a large extent. This improved TEC shows that building strong magnetocrystalline coupling can effectively improve the cooling capacity.

Claims

1. A preparation method for constructing a strong magnetocrystalline coupling alloy, characterized in that: The specific steps include: Step 1, based on Tb5Si2Ge (2-x) Co x The alloy molecular formula, wherein x=0.1-0.2, uses high-purity Tb, Si, Ge and Co elements for precise proportioning; weighs each raw material according to the required sample weight requirements, mixes them evenly and places them in a crucible of a smelting furnace; then seals the furnace chamber, introduces inert gas, heats and melts, and cools to room temperature in an inert gas environment; according to the above steps, adjusts the sample orientation, and repeatedly melts 4-5 times to obtain an alloy ingot; Step 2, using a superconducting quantum interference device to measure the magnetic properties of the alloy; Step 3: Use Maxwell's relation to calculate the magnetic entropy change ΔS of the alloy. M , and then use the temperature average entropy change to determine the magnetic refrigeration capacity of the alloy; In the step 2, a superconducting quantum interference device is used to measure the isothermal magnetization MH curve of the sample at different temperatures; In step 3, the magnetization MH curve obtained in step 2 is used, and then the Maxwell relation is used to calculate the Calculate the magnetic entropy change ΔS of the alloy M , where T is the test temperature, H is the magnitude of the external magnetic field, and μ0 is the vacuum permeability. In order to evaluate the refrigeration capacity, the average entropy change of temperature is introduced and written as Here ΔT lift and T mid Respectively represent the temperature range and center temperature, ΔS(T) ΔH It represents the entropy change value of the variable magnetic field at a specific temperature.

2. A method for preparing a strong magnetocrystalline coupling alloy according to claim 1, characterized in that: In the step 1, the smelting method is cold crucible suspension smelting, and the inert gas is high-purity argon.